Company Capability as a Driver of Corporate Sustainability Performance in the Submarine Cable Ecosystem in Indonesia - Nanang Hendarno; Sulaeman Rahman Nidar (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to test and analyze the influence of company capability on corporate sustainability performance in the submarine cable industry in Indonesia. The study uses a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis method. The research population is 27 companies operating in the submarine cable industry in Indonesia. The results of this study show the significant role of company capability in driving corporate sustainability performance in the submarine cable ecosystem in Indonesia. Technological capability is a dimension that plays a dominant role in strengthening company capability in supporting the achievement of corporate sustainability performance. The results of this study provide a theoretical contribution by integrating RBV and dynamic capability in the framework of the submarine cable industry in Indonesia. The managerial implication for corporate management in the submarine cable ecosystem in Indonesia, is the need for strategic investment in technology capabilities.